Care for minors in medieval town statutes at the juncture of the Holy Roman Empire and the Republic of Venice, with a note on the reception of Roman law - Kambič, Marko (Acta Histriae, 2021)
This paper analyses and compares statutory provisions on tutelage for minor children in the Venetian towns of Koper, Izola, and Piran, and compares them with the regulation of the town of Ptuj, which was part of the Holy Roman Empire. It draws on selected notations from the notary books of Piran and, indirectly, documentary sources from Ptuj that reflect the practice corroborating and illustrating findings concerning statutory law. Moreover, from a comparative perspective, the paper aims to establish how Roman law influenced the legal regulation of the care of minor children in the two neighbouring territories that differed in terms of tradition and administrative affiliation.
Keywords: Istra; Izola; Koper; otroci; Piran; Ptuj; recepcija rimskega prava; skrb za mladoletne osebe; skrbniki; varuhi